2009
DOI: 10.3113/fai.2009.1202
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Anatomy of the Proximal Release of the Gastrocnemius: A Cadaveric Study

Abstract: We conclude that the approach to the medial head of gastrocnemius is free from neurovascular structures and that release of the medial head alone may be efficacious in the operative treatment of isolated gastrocnemius tightness that has failed non-operative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 7 publications
(7 reference statements)
0
13
0
2
Order By: Relevance
“…The medial head was found to be much larger in both the muscular and aponeurotic components than the lateral head in all specimens. On average the cross-sectional area of the aponeurosis of the medial head of gastrocnemius was 2.4 times the crosssectional area of the aponeurosis of the lateral head [21]. The medial head is supposed to account for most of the gastrocnemius tightness.…”
Section: Discussionmentioning
confidence: 94%
“…The medial head was found to be much larger in both the muscular and aponeurotic components than the lateral head in all specimens. On average the cross-sectional area of the aponeurosis of the medial head of gastrocnemius was 2.4 times the crosssectional area of the aponeurosis of the lateral head [21]. The medial head is supposed to account for most of the gastrocnemius tightness.…”
Section: Discussionmentioning
confidence: 94%
“…Compared with the lateral head of the gastrocnemius, the medial head is wider, thicker and tighter, and with less complicated and variable neurovascular structures nearby [18,21]. A recent anatomic study revealed that the superficial part of the Achilles tendon is mainly from the medial head of the gastrocnemius and has continuity with the plantar fascia [22].…”
Section: Discussionmentioning
confidence: 96%
“…The approach is safe with low risk of neurological complication, whereas approaches to the lateral head must be used with care due to the variable anatomy of nerves in that area. 41 Another benefit of PMGR is that only the tight aponeurosis is released, leaving the main muscle belly intact. The procedure does require the patient to be positioned either prone or 'lazy-lateral', but is conveniently performed as a day case with local anaesthetic and light sedation.…”
Section: Gastrocnemius Lengthening Procedures For Recalcitrantmentioning
confidence: 99%